Association between IL-17A rs2275913 gene polymorphism and the levels of inflammatory markers (NFKB1 and IL-17A) in Iraqi patients with diabetic nephropathy (T2DNP) - H. A. Alhour; R. A. Abdulkareem; H. H. K. Al-Shukri (Regulatory Mechanisms in Biosystems, 2025)
One of the most common complications of chronic kidney disease (CKD) is diabetic nephropathy (T2DNP), which is i n creasing worldwide. This study aimed to examine the association between IL-17A rs2275913 gene polymorphism and diabetic nephropathy (T2DNP) in Iraqi patients. This study included 150 participants divided into three groups: Control, T2DM ( T ype 2 diabetes mellitus) , and T2DNP. Inflammatory markers (IL-17A) were investigated following the protocol provide d with the ELISA kit. B riefly, the enzyme immunoassay s known as human NFKB1 and IL-17A were used to quantitatively and specif i cally identify these cytokines in human serum in vitro . The polymerase chain reaction method known as restriction fragment length polymorphism (PCR-RFLP) was used to detect the IL-17A rs2275913 SNP with specific utiliz ation of particular primer sequences. The study found that levels of NFKB1 and IL-17A were significantly higher in the diabetic groups (T2DM and T2DNP) compared to the C ontrol group. The C ontrol group had NFKB1 levels of 1.15 ± 0.28, while the T2DM and T2DNP groups had levels of 4.83 ± 1.49 and 8.56 ± 1.16, respectively. For IL-17A, the C ontrol group showed levels of 19.67 ± 1.85, while T2DM and T2DNP had levels of 43.04 ± 10.32 and 131.81 ± 13.13. The T2DN group exhibited the highest levels for both parameters, with a statistically significant p-value of 0.001 and the multinomial regression analysis examined the associ a tion between IL-17A gene polymorphism and T2DM/T2DNP. For the comparison of T2DM versus Control, the AA genotype had an odds ratio (OR) of 5.357, and the AG genotype had an OR of 2.857, both with significant p-values. In the T2DN versus Control comparison, the AA genotype had an OR of 6.562, and the AG genotype had an OR of 3.542, also significant. Ho w ever, no significant associations were found between IL-17A genotypes and T2DNP compared to T2DM. The study concludes that there is a significant correlation between IL-17A gene polymorphism and diabetic nephropathy (T2DNP) in Iraqi patients, that both T2DM and T2DNP groups had higher levels of the inflammatory markers NFKB1 and IL-17A than the C ontrol group, with the T2DNP group having the highest levels, and that certain IL-17A genotypes are associated with increased odds of developing T2DM and T2DN, but that there were no significant differences between T2DNP and T2DM in terms of IL-17A genotypes. These findings highlight the significance of IL-17A as a potential biomarker and genetic factor in the progression of diabetic nephropathy, suggesting directions for future research and clinical implications in managing diabetic nephropathy as a CKD complication.